Media reality in the Iraqi musical and lyrical art (Journal of the College of Basic Education, 2022)
Integrated media planning is planning that takes into account from the beginning the unity of media work in all its forms and forms, with the exploitation of all media and communication channels and their human and material elements and making them serve the supreme strategy of the general public. Therefore, media in the culture of arts in general and music in particular are among the most dangerous correspondences, and it is difficult without them to establish a coherent and integrated social life, and this means that there is a strong relationship between the media and the language of civilization.